Implementation of Management Functions in the Naqshbandi Tariqa: Building the Socio-Religious Values of Congregants in Bandar Tinggi Village/ Implementasi Fungsi Manajemen pada Tarekat Naqsyabandiyah: Membangun Nilai Sosial-Keagamaan Jamaah di Desa Bandar Tinggi - Davina Zahwa Purba; Syawaluddin Nasution (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2026)
This study aims to analyze the role of management in improving the socio-religious values ​​of the Naqsyabandiyah congregation in Bandar Tinggi Village. The focus of this study includes the application of management functions including planning, organizing, implementing, and supervising the congregation's activities, as well as the social values ​​formed among the congregation. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The informants for this study were determined by purposive sampling, consisting of administrators and congregations. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data review, and drawing conclusions. The findings indicate that management functions were implemented through deliberation in planning, task division in organizing, direction and guidance in implementation, and informal evaluation in supervision. The implementation of these functions contributed to strengthening the congregation members’ socio-religious values, as reflected in devotion, mutual assistance, kinship, and social concern. This research contributes to the development of studies on the management of da'wah and Sufism, particularly understanding the integration of management functions in the spiritual and social development of society.